Seven amazing uses for Hazel. - Ochs, Susie (Mac life)
Hazel is like a housekeeper of your Mac, and it's time to put her to work. If your Downloads folder is so stuffed with disk images, random MP3s, and PDF bank statements that you're starting to get afraid to look in there, you need Hazel. If your desktop is cluttered with so many icons that it takes more than 30 seconds to find one, you need Hazel. This uber-useful Systems Preference Pane lets you create rules to keep specific folders automatically organized and maintained, so it's perfect for those problems. But Hazel doesn't just move your files around--it can rename them, run scripts on them, snd so much more.